2013
DOI: 10.1111/gove.12023
|View full text |Cite
|
Sign up to set email alerts
|

Political Control and Managerial Survival in State‐Owned Enterprises

Abstract: This article explores the impact of political determinants on the survival of managers in state-owned enterprises (SOEs). Drawing on theories of bureaucratic delegation, it is argued that preference divergence between principals and agents as well as among principals is a major driver of managerial turnover. More specifically, the partisan affiliation of SOEmanagers with the government, the opposition, or individual ministers can serve to explain the length of their tenure. The analysis employs Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 65 publications
0
61
0
Order By: Relevance
“…This paper highlights foreign ownership, state ownership, dispersion of ownership, and the influence of a single powerful shareholder as potential ownership structure-related determinants that affect the use of internal audit. These determinants are based on prior studies (Aggarwal, Erel, Ferreira, & Matos, 2011;Carey, Knechel, & Tanewski, 2013;Collier & Gregory, 1999;Connelly, Hoskisson, Tihanyi, & Trevis Certo, 2010;Ennser-Jedenastik, 2014;La Porta et al, 1999;Leuz et al, 2010;Shleifer & Vishny, 1997;Thomsen & Pedersen, 2000).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…This paper highlights foreign ownership, state ownership, dispersion of ownership, and the influence of a single powerful shareholder as potential ownership structure-related determinants that affect the use of internal audit. These determinants are based on prior studies (Aggarwal, Erel, Ferreira, & Matos, 2011;Carey, Knechel, & Tanewski, 2013;Collier & Gregory, 1999;Connelly, Hoskisson, Tihanyi, & Trevis Certo, 2010;Ennser-Jedenastik, 2014;La Porta et al, 1999;Leuz et al, 2010;Shleifer & Vishny, 1997;Thomsen & Pedersen, 2000).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Such arguments have been developed in recent scholarship that has focused on the way in which governments throughout the world have maximised their patronage capacities to assert control over the delegated semi-state (e.g. Kopecky, Mair and Spirova, 2012;Ennser-Jedenastik, 2014), which in turn underlines a crucial distinction between 'patronage as corruption' and 'patronage as governance' (Flinders and Matthews, 2010 Whilst unexplored in the context of parliamentary democracy, a number of scholars have analysed legislative oversight of executive patronage in the context of presidentialism. In the US, the findings of the independent review of the appointments process (Twentieth Century Fund, 1996) were reiterated by several scholars, including Aberbach and Rockman (2009), who found that the complexity of the appointments process, the activism of Congress, and the political polarisation that often occurs across the separate branches of government had served to congest the system and encourage executive gaming.…”
Section: Principals Patronage and Parliamentary Democracymentioning
confidence: 99%
“…Ennser-Jedenastik, 2014;Kopecký, Mair and Spirova, 2012;Kopecký and Scherlis, 2008;Park and Kim, 2013).…”
mentioning
confidence: 99%
“…Despite wide-ranging privatisation programmes, SOEs are still and will be an important part of many economies, especially in developing economies (La Porta, Lopez-de-Silanes, & Shleifer, 1999;Ezzamel, Wilmott, & Worthington, 2008;Vagliasindi, 2008;Ennser-Jedenastik, 2013). According to the United Nations, SOEs in high-income countries constitute an 8% share of GDP and a 13% share of investments (Ernst & Young, 2010).…”
Section: Introductionmentioning
confidence: 99%